ANALYSIS OF PERSONIFICATION IN JUSTIN BIEBER’S ALBUM “PURPOSE” - Indah Fitriani, Annisaa; Ayiz, Abdul; Khadifa Abdul Rozzaq Wijaya, Rahmaditya (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study investigates the role of personification in Justin Bieber’s 2015 album Purpose, with a particular focus on how this figurative device enhances the album’s thematic and emotional dimensions. While previous studies on song lyrics have predominantly examined general themes or metaphorical expressions, limited scholarly attention has been given to the systematic use of personification in contemporary pop music. Employing a qualitative content analysis, this research examines all selected lyrics from the Purpose album, identifying and categorizing instances of personification and analyzing their functions in shaping meaning and listener engagement. The analysis reveals that Bieber frequently personifies abstract concepts such as time, love, memory, and freedom, as well as natural elements like wind and night, transforming them into active agents within the lyrical narrative. These personifications serve multiple functions, including emotional engagement, conceptual clarification, narrative enhancement, and thematic development. The findings suggest that personification is not merely a stylistic embellishment, but rather a fundamental narrative strategy that enriches the listener’s interpretive experience and deepens the affective resonance of the album. By demonstrating how figurative language elevates lyrical expression beyond entertainment, this study contributes to a broader understanding of the significance of personification in popular music and its role in mediating self-reflection, relational complexity, and existential themes.